Implementasi Kebijakan Kepala Madrasah dalam Meningkatkan Kompetensi Profesional Guru di MTS an Nawawiyah Kediri - Abdul Hadi (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Policies set by leaders of educational institutions are often in the spotlight of experts, both in science and other fields. The madrasah principal is fully responsible for the continuity and existence of the educational institution. The purpose of this study was to determine the implementation of the decision letter of the Head of MTs An Nawawiyah No 091 of 2023 and the professional competence of teachers at MTs An Nawawiyah Kepung Kediri. This research uses a qualitative approach with a case study type of research. Data collection techniques using interviews, observation and documentation. The data analysis technique uses Miles Huberman and Saldana's interactive data analysis model, including: data reduction, data display, and conclusion drawing. The results showed that: (1) An Nawawiyyah Madrasah Head Policy in improving teachers' professional competence. There are two main policy aspects implemented, namely macro and micro policies. Macro policies include curriculum planning which includes annual, semester, monthly, weekly, and daily work plans. Meanwhile, micro policies focus more on the internal arrangements of the madrasah which include programs such as PKG (Teacher Performance Assessment), PPG (Teacher Professional Education), MGMP (Musyawarah Guru Mata P1), training, workshops, meetings, coaching in the preparation of lesson plans, classroom supervision, question making, learning evaluation, asatidz/asatidzah board activities, and competitions. (2) The professional competence of teachers at MTs An Nawawiyah is at a good level, indicated by five main aspects: mastery of subject matter, ability to develop learning methods according to standards, utilization of media and learning resources, reflection on learning and participation in seminars and training, and awareness of the development of science and technology in carrying out tasks.